Pemetaan Pasar Dan Strategi Pemasaran Secara Islami Bagi Usaha Mikro Kecil Dan Menengah - Feti Fatimah; Mega Wahyu Rhamadanita; Mohammad Sofianto (RELASI : JURNAL EKONOMI, 2019)
The success of a strategy that has been established largely determined by how much the level of conformity of these strategies with environmental change, competition, as well as the situation of the company. Formulation of the problem in this research is how the mapping market and Islamic marketing strategies in the UMKM business field for Crafts in Jember Regency Balung. The location of this research in Jember Regency Balung. The results of his research is the result of matric Internal External SMEC was at quadrant V which means having Stability/growth strategy to develop future will come. the Islamic Marketing strategies can consist of applying a strategy of maintaining and sustaining, market penetration and product development. SWOT matrix analysis of the SMEC is a Islamic marketing strategy that is in S-O Strategies where this strategy consists of Utilizing Government programmes relating to enterprise development, Developing product quality and Expand market